The Preliminary Studies of Critical Thinking Skills on Subject of Matter and Their Changes on Middle Schooles - Listiyorini, Listiyorini; Marlina, Leni; Yusup, Muhamad; Rahman, Nor Farahwahidah Abdul (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to describe or provide an initial picture of the level of critical thinking skills of junior high school students on the subject of research and its changes in South Sumatra identfy and analyze preliminary studies of students critical thinking skills. Methodology: The methodology of this study is survey- quantitative descriptive research. Data collection techniques was carried out through critical thinking skill questions of matter and their changes. The research location is at Junior High School 1 Banyuasin Regency, South Sumatera. This Study sample consist of 139 Class 7 Students. Main Findings: The findings of this study of critical thinking skill average were Class 7A had an average percentage of 28.73% in the low category, class 7B had an average percentage of 61.83% in the high category, class 7C had an average percentage of 43.43% in the sufficient category, and class 7E had an average percentage of 32.32% in the low category. Overall, the average critical thinking skills of students was 41.34% in the sufficient category. Novelty/Originality of this study: The novelty of this research lies in the contribution of the research to students' skills in answering critical thinking questions on the concept of matter and its changes. The findings can provide new insights in the context of education and researchers to develop appropriate methods and strategies to improve students' critical thinking skills.